2001
DOI: 10.1037/1528-3542.1.3.320
|View full text |Cite
|
Sign up to set email alerts
|

Making meaning brings pleasure: The influence of titles on aesthetic experiences.

Abstract: The extent to which titles influence aesthetic experiences was examined in 3 experiments. Participants viewed and rated illustrations and photographs on understanding and qualities of the aesthetic experience (e.g., enjoyment, interest). The presence and type of title were manipulated across conditions and experiments. Metaphorical titles led to greater aesthetic experiences than either no title or descriptive titles (the elaboration effect). The elaboration effect occurred regardless of whether participants b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
225
5
4

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 210 publications
(273 citation statements)
references
References 13 publications
28
225
5
4
Order By: Relevance
“…For example, it has been theorized and shown that good mood, positive environments, and benign situations enhance abstract processing and inclusive categorization whereas bad mood, threatening environments, and insecure situations enhance a more concrete thinking style and exclusive categorization (Gasper & Clore, 2002;Isen & Daubman, 1984;Friedman & Förster, 2000, 2001Förster & Higgins, 2005; for a review see Friedman & Förster, 2007). Recently, we (Förster & Schimmel, under review) were able to show such subtle influences on attitudes toward conventional and unconventional arts.…”
Section: Implications For Real Lifementioning
confidence: 99%
“…For example, it has been theorized and shown that good mood, positive environments, and benign situations enhance abstract processing and inclusive categorization whereas bad mood, threatening environments, and insecure situations enhance a more concrete thinking style and exclusive categorization (Gasper & Clore, 2002;Isen & Daubman, 1984;Friedman & Förster, 2000, 2001Förster & Higgins, 2005; for a review see Friedman & Förster, 2007). Recently, we (Förster & Schimmel, under review) were able to show such subtle influences on attitudes toward conventional and unconventional arts.…”
Section: Implications For Real Lifementioning
confidence: 99%
“…Moreover, the range of effects was greater for appraisals of ability to understand The Appraisal Basis of Expertise A final experiment (Silvia, in press) applied the appraisal model to the study of artistic expertise. Many studies have revealed expert-novice differences in emotional responses to art (e.g., Hekkert & van Wieringen, 1996a, 1996bMillis, 2001). A typical finding in this area is that people with experience in art prefer works higher in complexity than do people without expertise in art (Hare, 1974;Walker, 1980).…”
Section: Within-person Relationships Of Appraisals and Interest In Artmentioning
confidence: 99%
“…These works demonstrated that people describe paintings differently after they read the title Franklin et al [1993]. Also, they postulate that title and description of paintings can improve the understanding Leder et al [2006] and the aesthetic evaluation Hristova et al [2011]; Millis [2001]. The influence of title and description is even more crucial for abstract artworks where the visual clues are open to interpretation.…”
Section: Related Workmentioning
confidence: 99%
“…Millis [2001] investigate the effects of metaphorical (or elaborative) and descriptive titles on the understanding, the level of emotional responses, interest, enjoyment, and elicited thoughts of artworks. He observed that metaphorical titles, increases the aesthetic experience more than no title or descriptive titles.…”
Section: Related Workmentioning
confidence: 99%